MAQĀṢID ALQUR’ĀN AL-GHAZALI DALAM KITAB SIRĀJ AŢ-ṬĀLIBĪN KARYA SYEKH IHSAN AL-JAMPESI - Cholid Ma`arif (QOF, 2020)
This article talked about maqāṣid al-Qur’ān on exegesis worked by Syaikh Ihsan Jampes, aspecially toward some verses at book of Sirāj aṭ-Ṭālibῑn vol. II. There are three questions should be answered; about the type of Quranic-exegesis, the operational process of Maqasid Alquran, and finally the main theme of Maqasid Alquran on the book of Sirāj aṭ-Ṭālibῑn vol. II. By using study of library-research and descriptive-analysis writing, automatically the researcher made those verses as object of material and the book as primary-object soon the other books as secondary, such as book of Jawāhir al-Qur’ān worked by al-Ghazali. The results of this research were; firstly, the book of Sirāj al-Ṭālibῑn uses type of tafsir isyari just to explain the majority exegesis of those verses within. Secondly, by modeling of maqāṣid al-Qur’ān arranged by al-Ghazali, the researcher found at least 80 main-verses on the book of Sirāj al-Ṭālibῑn, which is talking about knowing of Allah and the prophetic-wisdom are more dominate themes than about life of mankind. Thirdly, the implication of those, there are two big groups of maqāṣid following maqāṣid al-Qur’ān of alGhazali; monotheism-eschatology, and wellness during other themes such as morality, wisdom, Islamic science, and prosperity of mankind. Four of these big themes bring to some understanding that the main maqāṣid al-Qur’ān on the book of Sirāj aṭ-Ṭālibῑn is the wellness (kemaslahatan) on the world and hereafter for all mankind.